SURGICAL INFECTION OF SOFT TISSUES ON THE BACKGROUND OF DIABETES MELLITUS – WHAT IS THE REASON FOR MAINTAINING UNSATISFACTORY RESULTS? (Western European Journal of Medicine and Medical Science, 2024)
Despite the rapid development of all spheres of healthcare, with the introduction of new methods of diagnosis and treatment, the problem of treating patients with various forms of surgical infection has not lost its relevance. Moreover, the contingent of severe forms of surgical soft tissue infection is increasing. The paper analyzes the main causes of the progression of surgical infection of soft tissues, focusing on the development of this pathology in patients with diabetes mellitus. The authors characterize the identified shortcomings in the treatment of patients with this pathology and indicate the necessary therapeutic and diagnostic measures. The work is based on the analysis of 795 patients over a five-year follow-up period.